Transition period: Pilot study on performance reduction of ability to jump in volleyball - Forte, D.; Ceciliani, A.; Izzo, R.; Altavilla, G. (Journal of Human Sport & Exercise, 2019)
As previously introduced in the preliminary study (Forte & Altavilla, 2018) we want to estimate the reduction in performance in the transition period, the purpose of this work is to expand the sample of data on the ability to jump. The method is experimental and the study was conducted on the same sample of 22 female athletes divided into two experimental groups, the first composed of athletes aged 12-16 years and the second on athletes aged 18-25 years. In all subjects the following parameters were assessed: height with a stretched arm and height with two extended arms. The elevation and coordination skills were evaluated with the Abalakov test using the technical gesture of the attack and the wall. Other data were obtained by evaluating the results obtained from the difference between the measurement of the attack and the height with an extended arm, and between that of the wall and the height with two extended arms. The test results showed significant reductions in ability to jump after the transition period.